Development of a framework of intervention strategies for point of care quality improvement at different levels of healthcare delivery system in India: initial lessons. (3rd August 2021) - Datta, Vikram; Srivastava, Sushil; Garde, Rahul; Mehta, Rajesh; Livesley, Nigel; Sawleshwarkar, Kedar; Pemde, Harish; Patnaik, Suprabha K; Sooden, Ankur; Singh, Mahtab; John, Susy Sarah; Pradeep, Jeena; et al.
Abstract : Background: Inadequate quality of care has been identified as one of the most significant challenges to achieving universal health coverage in low-income and middle-income countries. To address this WHO-SEARO, the point of care quality improvement (POCQI) method has been developed. This paper describes developing a dynamic framework for the implementation of POCQI across India from 2015 to 2020. Methods: A total of 10 intervention strategies were designed as per the needs of the local health settings. These strategies were implemented across 10 states of India, using a modification of the 'translating research in practice' framework. Healthcare professionals and administrators were trained in POCQI using a combination of onsite and online training methods followed by coaching and mentoring support. The implementation strategy changed to a fully digital community of practice platform during the active phase of the COVID-19 pandemic. Dashboard process, outcome indicators and crude cost of implementation were collected and analysed across the implementation sites. Results: Three implementation frameworks were evolved over the study period. The combined population benefitting from these interventions was 103 million. A pool of QI teams from 131 facilities successfully undertook 165 QI projects supported by a pool of 240 mentors over the study period. A total of 21 QI resources and 6 publications in peer-reviewed journals were also developed. The average cost of implementing POCQI initiatives for a target population of one million was US$ 3219. A total of 100 online activities were conducted over 6 months by the digital community of practice. The framework has recently extended digitally across the South-East Asian region. Conclusion: The development of an implementation framework for POCQI is an essential requirement for the initiative's successful country-wide scale. The implementation plan should be flexible to the healthcare system's needs, target population and the implementing agency's capacity and amenable to multiple iterative changes.